Identification of Shallow Aquifer Zone Using Vertical Electrical Sounding (VES) Method with Schlumberger Array. Case Study: Universitas Indonesia - Yuannisa Rustriandayani; Ayunda Aulia Valencia; Tsabita Rasyda Fadia (Lembaga Ilmu Pengetahuan Indonesia, 2023)
This study aims to identify shallow aquifers in Universitas Indonesia (UI). Fifteen vertical electrical sounding (VES) surveys were conducted using the Schlumberger array. The apparent resistivity from VES measurements was interpreted using curve matching inversion to obtain depth, thickness, and resistivity of subsurface layers, which is then compared with the literature and lithology log from boreholes. The result shows that subsurface layers in the study area consist of clay, sand, and silt. Sand layers are interpreted as aquifers because they have higher porosity and permeability than clay and silt layers. In addition, sand layers exhibit a resistivity range (< 300 Ωm) similar to other studies. Sand aquifers can be found at shallow depths (min 0.5 m) along the Northwest and Southeast of the study area. The sand aquifers are thicker within the campus than in the forest area (up to 12 m). This information is important in decision-making regarding groundwater search and utilisation in the UI area.